Survey among agricultural workers about interpretation of plant protection product labels and safety data sheets - Rubbiani, Maristella (Annali dell'Istituto superiore di sanita, 2010)
The objective of this work was to examine the effectiveness of risk communication in agriculture through examination and interpretation of safety data sheets and product labels for agriculture products classified as hazardous. Labels and safety data sheets were shown to the users inviting them to report their own interpretation of hazard, risk and the need of preventive measures. One area sample was identified in a cluster of wine companies, chosen in a range of medium to large sizes throughout the country, where 100 subjects were interviewed by telephone or direct interview. Participants were surveyed through questions relating to demographic information, education and perception of risk.